(untitled) - Plumley, Sue (Indianapolis, Ind., 1996)
The 10 Minute Guide to cc:Mail Release 6 is for users who need to be productive quickly with cc:Mail and who don't have time to read 20-50 page chapters on how to manage and maintain a mail system. The book teaches the basic features and functions of Lotus cc:Mail Release 6 in approximately 25 mini-tutorials, each of which can be completed in ten minutes or less.
Keywords: Electronic mail systems,Hệ thống thư điện tử